Mapas conceituais como recurso didático potencialmente significativo no ensino de ciências: uma experiência no nono ano do ensino fundamental : anos finais - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The research with Concept Maps (MCs) in the teaching-learning process in Science in Elementary School - Final Years is justified by its ability to simplify complex concepts, promote the structured organization of knowledge, and stimulate the active construction of students' understanding, making the learning process more effective and engaging. The main objective of this research was to understand how the use of CMs can contribute to the improvement of the teaching-learning process in this discipline. In the first chapter, entitled "Conceptual Bases and Theoretical Assumptions - Concept Maps", the development was divided into three subheadings. Initially, the didactic resources used in the teaching-learning process in Science were presented, emphasizing the importance of innovative methods to promote more meaningful learning. Then, the conceptual bases and theoretical assumptions related to KMs were addressed, highlighting their usefulness as a tool for representing knowledge and organizing ideas. The chapter one ended by exposing the fundamental principles and components of meaningful learning, which served as the basis for the teaching performance in research. In the second chapter "CMs and the Construction of Knowledge in Science Teaching", it consisted of a systematic literature review (RSL) with the objective of answering what are the contributions of concept maps to the construction of knowledge in Science teaching in the final years of elementary school? We selected 12 articles published between 2018 and 2022, which offered valuable insights into the use of CMs as a pedagogical tool to promote meaningful learning in Science. The third chapter described a practical experience in the teaching of Science using Concept Maps as a didactic resource. The research was conducted using the Action Research methodology, based on empirical foundations. The study was carried out in a ninth-grade class of elementary school in a state public school in the city of Anápolis-GO. Then, he detailed the application of the data collection instruments. It was decided to use a questionnaire and a semi-structured interview after the end of the three pedagogical intervention activities with the KMs. Both instruments contained five questions and were applied at different times and places. The questionnaire was administered on a single day, with the presence of all participants, while the interviews took place individually over three days. And, finally, the validation of the educational product developed was described, which consisted of a Didactic Manual for the Use of Concept Maps in Science Teaching. This manual was developed based on the evidence collected during the research and aimed to provide practical guidance for teachers interested in adopting this innovative approach in their science classes. In summary, this study contributed to the improvement of pedagogical practices in the context of science teaching, promoting a more meaningful and effective learning for students.
Concept maps as a potentially significant didactic resource in science teaching: an experience in the ninth year of elementary school : final years
Keywords: Mapas conceituais; Recurso didático; Ensino de ciências; Ensino fundamental; Aprendizagem significativa; Concept maps; Didactic resource; Science teaching; Elementary school; Meaningful learning; CIENCIAS HUMANAS::EDUCACAO; EDUCACAO::ENSINO-APRENDIZAGEM